2017
DOI: 10.1371/journal.pone.0178724
|View full text |Cite
|
Sign up to set email alerts
|

Acute 40% exchange-transfusion with hemoglobin-vesicles in a mouse pneumonectomy model

Abstract: ObjectivesHemoglobin vesicles (HbVs) function as a red blood cell (RBC) substitute and are composed of purified hemoglobin encapsulated in a phospholipid bilayer membrane. The performance of HbVs as a substitute for RBC transfusions was examined in a mouse model of pneumonectomy following acute 40% exchange-transfusion with HbVs.MethodsBefore performing left pneumonectomies, 40% of the blood volume of mice was replaced with a) lactated Ringer’s solution (control), b) 5% recombinant human serum albumin (rHSA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
(35 reference statements)
3
9
0
Order By: Relevance
“…The short-term to long-term effects of normal HbV infusion have been evaluated in a mouse pneumonectomy model in which 40% of circulating blood was exchanged with an HbV solution 24. All the pneumonectomised mice survived after acute isovolemic haemodilution with HbV suspended in serum albumin, although half of the mice died after albumin transfusion without oxygen carriers, similar to the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…The short-term to long-term effects of normal HbV infusion have been evaluated in a mouse pneumonectomy model in which 40% of circulating blood was exchanged with an HbV solution 24. All the pneumonectomised mice survived after acute isovolemic haemodilution with HbV suspended in serum albumin, although half of the mice died after albumin transfusion without oxygen carriers, similar to the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Although Hb-Vs are small in comparison to RBCs, they are large compared to macromolecules ( Figure 3 ) and accordingly do not generate a colloid osmotic pressure. The half-life of Hb-Vs is two to three days, which limits their use [ 66 , 67 ]. A few studies have reported on the use of Hb-Vs in porcine and rat MP models for livers and limbs [ 63 , 68 , 69 ].…”
Section: Overview Of Oxygen Carriersmentioning
confidence: 99%
“…HbVesicles do not contribute to the colloid osmotic pressure. HbVesicles have been studied in preclinical animal blood exchange and hemorrhagic shock models and were also tested in different areas such as isolated organ perfusion, extracorporeal membrane oxygenation priming, apnoe and two-dimensional cell cultures (Kohno et al, 2017;Sakai, 2017).…”
Section: Update On Concepts Of Artificial Oxygen Carriersmentioning
confidence: 99%